Two Versions of Lah Bako Dance: Representing Agricultural Working Class and Identity Creation - Prasetyo, Hery; Rosa, Dien Vidia; Astuti, Restu Puji; Satria, Ramadana Tahta; Ramadani, Rifki Dwi; Permata, Ayu Dinda; Ambarwati, Sagita Dwi (Institut Agama Islam Negeri Madura, 2019)
This article discusses the politics of identity in dance representations. Lah Bako dance is one of the Jember icons that was created to build an image of the tobacco farmers' culture. This dance is performed by women who represent the tobacco production process. However, the practical needs that are framed through aesthetic motions present a new form of how women are positioned in agricultural societies. In this context, the Lah Bako dance becomes an instrument to create new meanings for women and also becomes an imaginary space for tobacco farming. The article discusses two main points: first, the Lah Bako dance became an integral part of government’s project to construct mass memories in the relations of production in the tobacco sector, and the second is women as subjects representing a farmer’s spirit which is formed as a new figuration that fluid and changeable as political image that transcended existing experimental conditions. An addition point highlighted in this article was the emergence of Islamic values in a dance version which is accomodated the elite interest of Jember’s identity slogan formation. Reseachers use Stuart Hall’s cultural representation and ethnography method to narrate the identity. This research found that the Lah Bako dance is constructed in dominant cultural formations that are legitimized by the structure of the regional government bureaucracy. Furthermore, it is crucial to criticize the space for voicing farmers’ subjectivity and class politics, which has been muddled from the elite network. The problem appears as a paradox for creating aesthetic reality through art, where the symbolic form can be enjoyed without touching inequality that continually arises.